2007
DOI: 10.1080/15715124.2007.9635331
|View full text |Cite
|
Sign up to set email alerts
|

Revised equations for Manning's coefficient for Sand‐Bed Rivers

Abstract: The procedure for selecting values of Manning n is subjective and requires judgment and skill which are developed primarily through experience. Government agencies and private sectors in developed nations such as the USA are still doing research on predicting n values for rivers. Since flow and boundary roughness vary with river conditions, such research is therefore pertinent for rivers in Malaysia where floods are one of primary concerns. Research on Manning n value was started by River Engineering and Urban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 8 publications
1
13
0
Order By: Relevance
“…Five values of Manning's coefficient were evaluated for this sandy, meandering stream: 0.01, the original 0.02, 0.03, 0.035 and 0.04. All of the evaluated values were within the range of those recorded in previous literature (Ghani et al, 2007;Land and Water Australia 2009). Arcement and Schneider (1989) found that streambed roughness tends to increase with particle size, degree of meandering and irregularity.…”
Section: Model Calibrationsupporting
confidence: 69%
“…Five values of Manning's coefficient were evaluated for this sandy, meandering stream: 0.01, the original 0.02, 0.03, 0.035 and 0.04. All of the evaluated values were within the range of those recorded in previous literature (Ghani et al, 2007;Land and Water Australia 2009). Arcement and Schneider (1989) found that streambed roughness tends to increase with particle size, degree of meandering and irregularity.…”
Section: Model Calibrationsupporting
confidence: 69%
“…Study Area. Perak is the second largest state in Malaysia in terms of land area (21 006 km 2 ) (Ghani et al, 2007). It is bordered by Thailand and Kedah in the north, Penang in the northwest, Kelantan and Pahang in the east, Selangor in the south, and the Malacca Strait to the west (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…It was constructed in 2000 with the intention of raising the water supply of Perak by 25%. This dam can provide 639,000 m 3 of water daily and is expected to satisfy the water demand in Kinta Valley until 2020 (Ghani et al, 2007).…”
Section: Study Areamentioning
confidence: 99%
“…The capital of Perak is the city of Ipoh. It is situated in Kinta Valley which overlies a limestone bed that is overlooked by limestone outcrops and bounded by the Kledang and Titiwangsa granite ranges from the west and east, respectively (Ghani et al, 2007).…”
Section: Study Areamentioning
confidence: 99%